A MOF-derived MXene / Co / C composite absorbing material and preparation method thereof

The MXene/Co-MOF composite was prepared and annealed by room temperature chemical solution method, which solved the problems of poor impedance matching and narrow frequency band of existing microwave absorbing materials, and achieved high-performance microwave absorption and electromagnetic shielding effects.

CN114614272BActive Publication Date: 2025-03-18FUJIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210219574.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-08
Publication Date
2025-03-18
Estimated Expiration
2042-03-08

AI Technical Summary

Technical Problem

Existing microwave absorbing materials have problems such as poor impedance matching, narrow frequency band, heavy mass, and thick thickness, which are difficult to meet the requirements of high-quality absorbing materials.

Method used

MXene/Co-MOF composites were prepared by room temperature chemical solution method, and Co-MOF-derived MXene/Co/C composite absorbing material was obtained by annealing to improve the impedance matching and microwave absorption performance of the material.

Benefits of technology

It realizes high-performance microwave absorption, has a multi-layer ordered channel structure, adjustable components and structure, which can effectively improve the impedance matching and frequency bandwidth of the material, and is suitable for microwave absorption and electromagnetic shielding and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114614272B_ABST
    Figure CN114614272B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method of a MOF-derived MXene / Co / C composite absorbing material, which is applicable to the field of microwave absorption. The present invention uses MXene as a substrate, composites it with Co-MOF, and anneals the obtained MXene / Co-MOF composite to obtain a novel MOF-derived MXene / Co / C nanocomposite absorbing material. After calcination, the MXene in the composite still maintains a multilayer sheet structure; the Co-MOF is transformed into a Co / C composite composed of graphite carbon and Co metal particles, and many evenly distributed carbon nanotubes (CNTs) with Co particles at the tip grow on its surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microwave absorption, and in particular to a MOF-derived MXene / Co / C composite microwave absorbing material and a preparation method thereof. Background Art

[0002] With the advent of the 5G era, the widespread use of various electronic products has brought convenience to people's lives, but it has also produced electromagnetic pollution that cannot be ignored. At the same time, in the military field, excellent absorbing materials have important scientific research significance for radar stealth technology, detector technology and precision weapon equipment research. Therefore, the research and development of high-performance microwave absorbing materials has received widespread attention. Although carbon materials have certain absorbing properties, they are non-magnetic and have high conductivity. The loss mechanism is single, mainly resistive loss. When used alone, they have the disadvantages of poor impedance matching, low attenuation ability and narrow bandwidth. Magnetic metals (such as Fe, Co, Ni) and their oxides have high density, poor corrosion resistance and poor impedance matching, and are usually not used alone as absorbing materials. In order to meet the requirements of high-quality absorbing materials such as "strong absorption, wide bandwidth, light weight and thin thickness", the composite of lightweight carbon-based materials and magnetic metal materials to obtain new carbon-based composite absorbing materials has become a research hotspot.

[0003] MXene is a typical representative of two-dimensional materials, with advantages such as large specific surface area, multiple active sites, adjustable chemical composition, and good electron conduction and storage capacity. However, single MXene has poor microwave absorption performance due to its high conductivity. The MXene obtained by HF etching has a microwave absorption performance of -11dB. On this basis, the MXene is modified, such as annealing the MXene obtained by HF etching, and the microwave absorption performance of the surface-modified MXene is significantly improved.

[0004] At the same time, the study of metal organic framework (MOFs) derived absorbing materials can realize the introduction of magnetic metals into carbon materials. MOFs have the characteristics of adjustable chemical structure, large specific surface area, multiple metal coordination sites, and diverse morphology. After annealing, MOFs can not only maintain the original morphological structure and porous structure, but also generate metal particles, graphite carbon and defects, which can effectively improve the impedance matching of materials and achieve multiple electromagnetic wave losses. Using Ni-MOF derived one-dimensional CNTs and two-dimensional Ti3C2T x At the same time, a three-dimensional conductive network is constructed to form a superstructure composite material. The composite material has an optimal reflection loss of -57.78dB when the impedance matching thickness is only 1.49mm. Therefore, the composite material of metal organic framework-derived magnetic material and carbon material is an ideal lightweight absorbing material. At present, there are relatively few studies on MOFs-derived absorbing materials, and the impedance matching of the materials needs to be further improved.

[0005] In order to improve the shortcomings of single carbon materials and magnetic materials as microwave absorbing materials, the present invention prepares MXene / Co-MOF by a room temperature chemical solution method, and then obtains a Co-MOF-derived MXene / Co / C composite absorbing material by annealing, which is applied to the field of microwave absorption. Summary of the invention

[0006] The object of the present invention is to provide a MOF-derived MXene / Co / C composite microwave absorbing material and a preparation method thereof. The composite microwave absorbing material has a simple preparation method, good dispersibility of magnetic components, and excellent microwave absorption performance.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a MOF-derived MXene / Co / C composite absorbing material comprises the following steps:

[0009] (1) Preparation of MXene: Ti3AlC2 powder is added to HF solution, heated in a water bath, and the product is washed and dried to obtain MXene;

[0010] (2) Preparation of Co-MOF: Cobalt salt and organic ligand are dissolved in solvents to obtain solution A and solution B. Solution B is added to solution A to obtain a mixed solution, and the mixture is reacted under magnetic stirring at room temperature for a period of time. The product is washed and dried to obtain Co-MOF.

[0011] (3) Preparation of MXene / Co-MOF composite: The MXene prepared in step (1) is placed in a solution containing a cobalt salt to obtain a solution C. The organic ligand is dissolved in a solvent to obtain a solution D, and then the C and D solutions are uniformly mixed and reacted under magnetic stirring, and finally the product is washed and dried to obtain a MXene / Co-MOF composite.

[0012] (4) Preparation of MXene / Co / C composite: The MXene / Co-MOF composite prepared in step (3) is annealed to obtain a MXene / Co / C composite absorber.

[0013] Furthermore, the weight percentage of HF in step (1) is 40wt%.

[0014] Furthermore, the washing in step (1) is performed by centrifuging with deionized water several times until the pH value of the supernatant is 6-7.

[0015] Furthermore, the cobalt salt described in step (2) is Co(NO3)·6H2O.

[0016] Furthermore, the solvent in step (2) is deionized water, methanol, a deionized water / methanol mixture (volume ratio of 1:1), ethanol, or N,N-dimethylformamide.

[0017] Furthermore, the reaction time of step (2) is 12 to 24 hours.

[0018] Furthermore, the organic ligand in step (2) is 2-methylimidazole.

[0019] Furthermore, in step (2), the mass of MXene in the MXene / Co-MOF composite varies in the range of 0 to 0.2 g.

[0020] Furthermore, the annealing atmosphere in step (4) is N2 gas and Ar gas.

[0021] Furthermore, the annealing temperature in step (4) is 500-1000°C.

[0022] Furthermore, the heating rate in step (4) is 0.5 to 5°C / min.

[0023] Furthermore, the annealing time in step (4) is 1 to 8 hours.

[0024] The present invention adopts a room temperature chemical solution method to prepare MXene / Co-MOF, and prepares surface-modified MXene and Co-MOF-derived MXene / Co / C composite absorbing materials by calcination; Co-MOF, as a precursor of the absorbing composite material, can provide a high specific surface area, adjustable composition and structure; after carbonization, the absorbing material has more pores and lower density, thereby reducing the filling ratio during application, thereby achieving lightweight.

[0025] The present invention has the following advantages:

[0026] (1) The MXene in the composite of the present invention still maintains a multi-layered sheet structure; Co-MOF is transformed into a Co / C composite composed of graphite carbon and Co metal particles, and many evenly distributed carbon nanotubes (CNTs) with Co particles at the tip grow on its surface. By adjusting the size of Co-MOF and the content of MXene in the MXene / Co-MOF composite, the prepared MXene / Co / C composite absorber has a multi-layered ordered pore structure, adjustable composition, structure and electromagnetic parameters.

[0027] (2) Combining carbon materials and magnetic materials, compared with a single absorbing material, multiple interfaces have multiple loss mechanisms and can effectively improve the impedance matching of the material.

[0028] (3) The MXene / Co / C composite absorbing material prepared by the present invention has a simple preparation process and excellent microwave absorption performance, and can guide the preparation of other magnetic MOF-derived C composite absorbing materials.

[0029] (4) In the composite structure, the polyhedral structure formed by the MXene sheets and the Co-MOF derivative is conducive to the multiple reflection and refraction of electromagnetic waves, the carbon nanotubes on the surface of graphite carbon can form a conductive network, and the magnetism of the Co metal particles is conducive to improving the impedance matching of the composite. The above characteristics can effectively improve the microwave absorption performance of the composite material. The MOF-derived MXene / Co / C composite material prepared by the present invention has the advantages of light weight, strong wave absorption ability, wide absorption bandwidth, thin matching thickness, etc., and has potential application prospects in the fields of microwave absorption, electromagnetic shielding, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 SEM images (a: Co-MOF-1; b: Co-MOF-2; c: Co-MOF-3) and particle size distribution diagrams (d: Co-MOF-1; e: Co-MOF-2; f: Co-MOF-3) of the Co-MOF materials prepared in Examples 1 to 3;

[0031] Figure 2 SEM images of the MXene / Co-MOF materials prepared in Examples 4 to 8 and the MXene / Co / C-1 prepared in Example 4 (a: MXene; b: MXene / Co-MOF-1; c: MXene / Co-MOF-2; d: MXene / Co-MOF-3; e: MXene / Co-MOF-4; f: MXene / Co-MOF-5; g to i: MXene / Co / C-1);

[0032] Figure 3 TEM image of MXene / Co / C-1 prepared in Example 4;

[0033] Figure 4 XRD patterns of the materials prepared in Examples 1 to 8 (a: before annealing; b: after annealing);

[0034] Figure 5 Reflection loss diagram of the MXene / Co / C composite absorber prepared in Examples 1 to 8 (a: Co / C-1; b: MXene / Co / C-1; c: MXene / Co / C-2; d: MXene / Co / C-3; e: MXene / Co / C-4; f: MXene / Co / C-5);

[0035] Figure 6Impedance matching diagrams of the MXene / Co / C composite absorbing materials prepared in Examples 1 to 8 (a: Co / C-1; b: MXene / Co / C-1; c: MXene / Co / C-2; d: MXene / Co / C-3; e: MXene / Co / C-4; f: MXene / Co / C-5);

[0036] Figure 7 This is the hysteresis loop diagram of the MXene / Co / C-1 composite absorbing material prepared in Example 4. DETAILED DESCRIPTION

[0037] In order to better illustrate the present invention, the applicant cites the following embodiments, which are only intended to explain the present invention and are not intended to limit its contents.

[0038] Example 1: Preparation of MXene

[0039] First, add 5 g of Ti3AlC2 powder in small amounts to 50 mL of HF acid solution and stir magnetically in a water bath at 60 °C for 24 h. Secondly, wash the solution with deionized water several times until it is neutral. The centrifugal speed of the centrifuge is 6000 rpm for 3 min. Finally, dry the washed sample in a vacuum oven at 60 °C for 24 h. The dark gray powder after drying is MXene.

[0040] Example 2: Preparation of Co-MOF

[0041] 0.9 g Co(NO3)2.6H2O was added to 24 mL deionized water and ultrasonicated for 10 min to obtain liquid A. 11 g 2-methylimidazole was added to 16 mL deionized water and ultrasonicated for 10 min to obtain liquid B. Under magnetic stirring, liquid B was slowly added dropwise to liquid A and reacted at room temperature for 24 h to obtain a purple solution. The purple solution was then washed with methanol for 4 to 5 times, and the sample was dried in a vacuum oven at 60 ° C for 24 h. The dried product was named Co-MOF-1.

[0042] Example 3 and Example 4

[0043] The preparation process was the same as that in Example 2, except that the solvent was changed and the reaction time was adjusted (conditions are shown in Table 1). The prepared samples were named Co-MOF-2 and Co-MOF-3, respectively.

[0044] Example 5: Preparation of MXene / Co-MOF-1 and MXene / Co / C-1 composites

[0045] 0.1g MXene and 0.9g Co(NO3)2.6H2O were added to 24mL deionized water and ultrasonicated for 10min to fully dissolve and obtain liquid A. Then 11g 2-methylimidazole was added to 160mL deionized water and ultrasonicated for 10min to obtain liquid B; then, liquid B was slowly added dropwise to liquid A under magnetic stirring and reacted at room temperature for 24h to obtain a blue-purple solution; after washing the blue-purple solution with methanol for 4 to 5 times, the sample was placed in a vacuum oven at 60℃ and dried for 24h to obtain a blue-purple powder named MXene / Co-MOF-1.

[0046] The sample was annealed in a N2 atmosphere, heated from room temperature to 800°C at 5°C / min and kept warm for 2h. The black powder after annealing was the MXene / Co / C-1 composite material.

[0047] Embodiment 6-9

[0048] Similar to Example 5, the solvent type, reaction time and component ratio were changed (conditions are shown in Table 1), and samples before and after annealing were obtained, which were named MXene / Co-MOF-2, MXene / Co-MOF-3, MXene / Co-MOF-4, MXene / Co-MOF-5, MXene / Co / C-2, MXene / Co / C-3, MXene / Co / C-4 and MXene / Co / C-5, respectively.

[0049] Table 1 Experimental material formula

[0050]

[0051]

[0052] The samples obtained in Examples 1 to 9 were characterized by scanning electron microscopy, transmission electron microscopy, X-ray powder diffraction, comprehensive physical property measurement system, network vector analyzer, etc. The specific test results are as follows: Figures 1 to 7 shown.

[0053] Figure 1 This is a SEM image of Co-MOF. It can be seen that Co-MOF is polyhedral with uniform width and narrowness distribution; the particle sizes of Co-MOF-1, Co-MOF-2 and Co-MOF-3 are significantly different. Combined with the particle size distribution diagram, it can be seen that the average particle size of Co-MOF-1 is about 2μm, and the average particle sizes of Co-MOF-2 and Co-MOF-3 are significantly reduced, about 400nm and 260nm respectively.

[0054] Figure 2 For the SEM images of each sample. Figure 2 As shown in a, MXene is in the form of lamellar sheets; Figure 2 In b-d, as the particle size of Co-MOF decreases, MXene is wrapped more and more tightly by Co-MOF. When the amount of MXene increases, the distribution of Co-MOF becomes sparse ( Figure 2 e and 2f). After carbonization, the MXene in MXene / Co-MOF still maintains a lamellar structure, while the Co / C derived from Co-MOF presents a collapsed polyhedral structure ( Figure 2 g~i).

[0055] Figure 3 This is the TEM image of MXene / Co / C-1. It can be clearly seen from the figure that many carbon nanotubes with Co metal particles on the tip are generated on the surface of the composite.

[0056] Figure 4 The XRD patterns of the samples before and after annealing are shown in Figure 1. The characteristic peaks of each component in the figure further prove that MXene, Co-MOF, MXene / Co-MOF and MXene / Co / C are successfully prepared.

[0057] Figure 5 is the loss diagram of the sample. Figure 5 As can be seen in a, the Co-MOF derivative Co / C has poor absorption performance, with a minimum reflection loss of only -9.04 dB; after being compounded with MXene, as the particle size of Co-MOF increases, the absorption performance of the MXene / Co / C composite increases accordingly ( Figure 5 b~d). Among them, MXene / Co / C-1 has the best absorption performance, which can reach -45.48dB. In addition, increasing or decreasing the proportion of MXene in the MXene / Co / C composite, such as Figure 5 As shown in Figures 5e and 5f, the microwave absorption performance of the composite material is significantly deteriorated.

[0058] Figure 6 The impedance matching diagram of the samples. It can be seen from the figure that MXene / Co / C-1 has the best impedance matching, and the area with the impedance matching value closest to 1 is the largest, while the impedance matching values ​​of other samples are almost not close to 1. Figure 7 The hysteresis loop of MXene / Co / C-1 shows that the Ms of the MXene / Co / C-1 composite material is 0.38 em u / g, which shows weak magnetism.

Claims

1. A method for preparing a MOF-derived MXene / Co / C composite absorbing material, characterized in that: The following steps are involved: Step (1) preparing MXene: adding Ti3AlC2 powder to HF solution, heating in a water bath, washing and drying the product to obtain MXene; Step (2) preparing Co-MOF: dissolving a cobalt salt and an organic ligand in a solvent respectively to obtain a solution A and a solution B; adding the solution B to the solution A to obtain a mixed solution, subjecting the mixture to magnetic stirring for reaction, and washing and drying the product to obtain Co-MOF; The cobalt salt described in step (2) is Co(NO3)·6H2O; Step (3) preparing a MXene / Co-MOF composite: placing the MXene prepared in step (1) in a solution containing a cobalt salt to obtain a solution C; dissolving the Co-MOF prepared in step (2) in a solvent to obtain a solution D; Under continuous stirring, liquid C and liquid D are uniformly mixed and reacted, and the product is washed and dried to obtain a MXene / Co-MOF composite; Step (4) preparing a MXene / Co / C composite: annealing the MXene / Co-MOF composite prepared in step (3) to obtain a MXene / Co / C composite absorbing material; In step (4), the heating rate is 0.5-5°C / min; the annealing temperature is 500-1000°C; the annealing time is 1-8h; and the annealing atmosphere is N2 gas or Ar gas.

2. The method for preparing a MOF-derived MXene / Co / C composite absorbing material according to claim 1, characterized in that: The weight percentage of the HF solution in step (1) is 35-45 wt%.

3. The method for preparing a MOF-derived MXene / Co / C composite absorbing material according to claim 1, characterized in that: The washing in step (1) is performed by centrifugation with deionized water for multiple times until the pH value of the supernatant is 6-7.

4. The method for preparing a MOF-derived MXene / Co / C composite absorbing material according to claim 1, characterized in that: The solvent in step (2) is at least one of deionized water, methanol, ethanol, and N,N-dimethylformamide.

5. The method for preparing a MOF-derived MXene / Co / C composite absorbing material according to claim 1, characterized in that: The reaction time of step (2) is 12 to 24 h.

6. The method for preparing a MOF-derived MXene / Co / C composite absorbing material according to claim 1, characterized in that: The organic ligand in step (2) is 2-methylimidazole.

7. The method for preparing a MOF-derived MXene / Co / C composite absorbing material according to claim 1, characterized in that: The mass of MXene in the MXene / Co-MOF composite in step (3) varies from 0 to 0.2 g.

8. A MOF-derived MXene / Co / C composite absorbing material prepared by the preparation method according to any one of claims 1 to 7.